The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1117/1.jbo.19.3.038002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sealing and cutting of porcine blood vessels,ex vivo, using a high-power, 1470-nm diode laser

Abstract: Abstract. Suture ligation with subsequent cutting of blood vessels to maintain hemostasis during surgery is time consuming and skill intensive. Energy-based electrosurgical and ultrasonic devices are often used to replace sutures and mechanical clips to provide rapid hemostasis and decrease surgery time. Some of these devices may create undesirably large collateral zones of thermal damage and tissue necrosis, or require separate mechanical blades for cutting. Infrared lasers are currently being explored as alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Given this, it is paramount to have an objective method with which vessel seals can be evaluated so that the hemostatic capabilities of laser-based systems can be tested. Current methodologies used for this purpose include burst pressure analysis (BPA), [9][10][11] microscopy, 12 and visual examination. [13][14][15][16] While BPA yields valuable insight as to the strength of seals, it cannot be performed in situ without invasive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Given this, it is paramount to have an objective method with which vessel seals can be evaluated so that the hemostatic capabilities of laser-based systems can be tested. Current methodologies used for this purpose include burst pressure analysis (BPA), [9][10][11] microscopy, 12 and visual examination. [13][14][15][16] While BPA yields valuable insight as to the strength of seals, it cannot be performed in situ without invasive measures.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,470 nm wavelength was found to seal porcine vessels of 1–6 mm diameter in less than 5 seconds. A subsequent study demonstrated faster sealing, transection of sealed tissue, increased burst strength, and greater safety margin . The laser sealed and cut ex vivo porcine renal arteries of 1–8 mm diameter in 2 seconds, yielding burst pressures greater than 1,200 mmHg and thermal coagulation zones less than 3 mm.…”
Section: Introductionmentioning
confidence: 92%
“…Our laboratory is currently exploring infrared (IR) lasers as an alternative energy modality for vessel sealing, capable of generating less collateral thermal damage. 21,22 Previous studies demonstrated the feasibility of sealing vessels in an open in vivo porcine model using a 1470-nm diode laser. 23 However, the initial prototype was designed for testing in open surgery and featured a plunger style tissue clasping mechanism and 12.7-mm outer-diameter optical components in the light delivery mechanism that were incompatible with standard laparoscopic surgical instruments and size constraints.…”
Section: Infrared Laser Vessel Sealingmentioning
confidence: 99%
“…Fresh porcine kidney pairs were obtained from a slaughterhouse (Spear Products, Inc., Coopersburg, Pennsylvania) and renal arteries were then dissected, cleaned of fat, and kept hydrated with saline for use within 24 h. The entire vascular tree for each kidney was carefully dissected and surgically exposed in a similar manner to previous studies, 21,22 providing multiple vessels with a wide range of diameters for testing. A total of 69 vessels were tested, ranging from 1.0 to 6.6 mm in diameter and with a mean diameter of 3.3 AE 1.7 mm.…”
Section: Tissue Preparationmentioning
confidence: 99%